2021
DOI: 10.1039/d0sc06969h
|View full text |Cite
|
Sign up to set email alerts
|

Coloring ultrasensitive MRI with tunable metal–organic frameworks

Abstract: As one of the most important imaging modalities, magnetic resonance imaging (MRI) still faces relatively low sensitivity to monitor low-abundance molecules. A newly developed technology, hyperpolarized 129Xe magnetic resonance imaging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Magnetic resonance can provide both spectroscopic and spatial information simultaneously, thus allowing parallel reading and imaging. Spectrally resolved MRI has been previously realized with various systems based on chemically different diamagnetic compounds 38 41 , host-guest interactions 42 , 45 , and lanthanide-induced NMR shifts 43 45 . The latter approach offers the advantage to select the NMR shifts without changing the chemical properties, which is particularly useful for in-vivo imaging applications 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance can provide both spectroscopic and spatial information simultaneously, thus allowing parallel reading and imaging. Spectrally resolved MRI has been previously realized with various systems based on chemically different diamagnetic compounds 38 41 , host-guest interactions 42 , 45 , and lanthanide-induced NMR shifts 43 45 . The latter approach offers the advantage to select the NMR shifts without changing the chemical properties, which is particularly useful for in-vivo imaging applications 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanides are ideally suited for this purpose, as they provide a range of chemically similar but magnetically different Ln 3+ ions amenable to stable incorporation into organic molecules via coordination 35 , 37 . While distinguishable NMR signals can be obtained from chemically different diamagnetic molecules and formulations 38 42 , introducing paramagnetic lanthanides allows for decoupling of the NMR shifts from chemical properties. This principle has been previously used to create chemically nearly identical molecules that could be spectrally resolved with magnetic resonance imaging (MRI) 43 45 .…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, the capability of 129 Xe hyper-CEST NMR was demonstrated for differentiating a complex mixture containing MOFs as nano-cages in which the latter displayed similar chemical compositions. This was possible by tuning the MOF structure and by encoding multiple false colors for observed Xe chemical shifts 56 . Saturation transfer (ST) techniques are a powerful tool that find an increasing number of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the flexible porosity confers MOFs as candidates of nanocarriers for loading different types of active ingredients involving small molecules, peptides/proteins, or nucleic acids with high loading capacity [ 12 , 13 ]. Furthermore, the unique optical and/or X-ray attenuation abilities of MOFs can be harnessed for molecular imaging, including fluorescence imaging, computed tomography [ 14 ], magnetic resonance imaging [ 15 ], and positron emission tomography [ 16 ]. For therapeutic applications, especially for phototherapy or radiotherapy, photosensitizers and high-Z elements acting as organizing molecular building blocks integrated into the MOFs will augment reactive oxygen species (ROS) production [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%